Barriers to convert to organic farming and the role of risk : an empirical application on Swedish data - Sterte, Åsa (SLU/Dept. of Economics, 2011)
To understand the motives, and perhaps more importantly the barriers, for farmers to convert from conventional to organic farming is of great interest for policy makers as well as for academics. In Sweden and in other EU countries, proposed targets of the area in organic farmland have failed to be reached in spite of different kinds of policy measures. Most studies agree that the average profitability seems to be comparable to or better in organic than in conventional farming. This would indicate that there must be other factors of importance which can explain the low particiapation rate. A higher perceived risk in organic farming with respect to yield and price is frequently brought up as a potential explanation within a qualitative framework. If farm income risk is higher in organic farming than conventional, a rational risk-averse individual would only convert if compensated by a sufficient risk premium. Therfefore, the observed hesitation of farmers to convert would be rational if income from organic farming is more risky and the risk premium is insufficient in compensating for this risk.